Offshoring and the Elasticity of Labour Demand - Neil Foster-McGregor; Johannes Pöschl; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2012)
This paper examines the impact of offshoring on labour elasticities for a sample of 40 countries over the period 1995-2009 using the recently compiled World Input-Output Database (WIOD). Including measures of narrow and broad offshoring, as well as indicators of manufacturing and services offshoring, in conditional and unconditional labour demand equations we find that offshoring has an overall neutral or slightly positive effect on employment. This result hides differences across industry types and across employment types however, with additional results indicating a negative effect of services offshoring in many industry types. Positive effects of other offshoring measures are found in high-tech manufacturing and for high-educated employment in particular.
Keywords: F16; J23; 330; labour demand elasticities; offshoring